(untitled) - Catarina Sousa Silva; Sónia Brandão; Ana Rita Azevedo; Ana Paula Prata (Central European Journal of Nursing and Midwifery, 2023)
Aim: To analyze the influence of sociodemographic, obstetric, childbirth, and breastfeeding variables on maternal self-efficacy in newborn care. Design: Descriptive cross-sectional study. Methods: The study was conducted in three hospital units in the Northern region of Portugal, with a non-probabilistic sample composed of 340 women recruited at postnatal wards on the day of hospital discharge. A questionnaire including the mother's sociodemographic, obstetric, childbirth, and breastfeeding data was used. For the analysis of maternal self-efficacy in newborn care, the Scale of Perceived Parental Self-Efficacy in Child Care was used. The scale is a 20-item self-report instrument developed to identify women with low levels of self-efficacy in newborn care. Descriptive and inferential statistics were used for data analysis. Results: Significant differences concerning maternal self-efficacy in newborn care were found with regard to level of education and parity, with multiparous women and women with lower levels of education presenting higher levels of self-efficacy in newborn care. Conclusion: The analysis of these variables could be valuable in building new knowledge to support the development of an action model that would allow at-risk women to be highly confident in their parenting role.